2014
DOI: 10.1175/mwr-d-14-00029.1
|View full text |Cite
|
Sign up to set email alerts
|

A Scale-Consistent Terrestrial Systems Modeling Platform Based on COSMO, CLM, and ParFlow

Abstract: A highly modular and scale-consistent Terrestrial Systems Modeling Platform (TerrSysMP) is presented. The modeling platform consists of an atmospheric model (Consortium for Small-Scale Modeling; COSMO), a land surface model (the NCAR Community Land Model, version 3.5; CLM3.5), and a 3D variably saturated groundwater flow model (ParFlow). An external coupler (Ocean Atmosphere Sea Ice Soil, version 3.0; OASIS3) with multiple executable approaches is employed to couple the three independently developed component … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
206
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 176 publications
(220 citation statements)
references
References 56 publications
1
206
0
Order By: Relevance
“…In a two-way coupling, the feedback is allowed, which leads to production of subgrid scale land surface fluxes and generally an improvement of model simulations (Zabel and Mauser 2013). It is argued that the coupled modeling approach has the advantage of including the soil moisture redistribution feedback in the lower boundary conditions of atmospheric models, which may lead to an improved representation of water and energy fluxes between land and atmosphere (Maxwell et al 2011;Shrestha et al 2014;Senatore et al 2015;Arnault et al 2016;Wagner et al 2016). Maxwell et al (2007) showed that the fully coupled modeling system yields a topographically driven soil moisture distribution and depicts a spatial and temporal correlations between surface and lower atmospheric variables and water depth.…”
Section: Introductionmentioning
confidence: 99%
“…In a two-way coupling, the feedback is allowed, which leads to production of subgrid scale land surface fluxes and generally an improvement of model simulations (Zabel and Mauser 2013). It is argued that the coupled modeling approach has the advantage of including the soil moisture redistribution feedback in the lower boundary conditions of atmospheric models, which may lead to an improved representation of water and energy fluxes between land and atmosphere (Maxwell et al 2011;Shrestha et al 2014;Senatore et al 2015;Arnault et al 2016;Wagner et al 2016). Maxwell et al (2007) showed that the fully coupled modeling system yields a topographically driven soil moisture distribution and depicts a spatial and temporal correlations between surface and lower atmospheric variables and water depth.…”
Section: Introductionmentioning
confidence: 99%
“…Kurtz et al (2016) recently provided a framework to couple PDAF with the land surface-subsurface part of the Terrestrial Systems Modelling Platform (TerrSysMP; Gasper et al, 2014;Shrestha et al, 2014). They showed the efficient use of parallel computational resources by TerrSysMP-PDAF, which is needed to simulate predicted states and fluxes over large 30 spatial domains and long simulations.…”
Section: Data Assimilation Frameworkmentioning
confidence: 99%
“…Discuss., https://doi.org /10.5194/hess-2018- Additionally, by selecting the ESA CCI soil moisture product for assimilation, the potential impact of a long term soil moisture observations on hydrologic simulations can be assessed for climate change studies. Moreover, CLM3.5 is also part of the fully coupled Terrestrial Systems Model Platform (TerrSysMP; Shrestha et al, 2014, Gasper et al, 2014, Keune et al, 2016) that simulates the full terrestrial hydrologic cycle including feedbacks between atmosphere, land-surface and subsurface compartments of the water cycle. The impact of satellite soil moisture assimilation on other water cycle variables 5 across the soil-vegetation-atmosphere system using TerrSysMP and its effects on the accuracy of model simulations at the continental scale remains to be explored.…”
mentioning
confidence: 99%
“…ParFlow parallel I/O is via task-local and shared files in a binary format for each time step. ParFlow is also part of fully coupled model systems such as the Terrestrial Systems Modeling Platform (TerrSysMP) (Shrestha et al, 2014) or PF.WRF (Maxwell et al, 2011), which can reproduce the water cycle from deep aquifers into the atmosphere.…”
Section: Test Case Experimental Designmentioning
confidence: 99%